Gender Expressions, Morality and the Use of Physical Force by the Argentine Police - Calandrón, Julieta Sabrina (2017)
This paper analyzes the phenomenon of the use of police force and gender moralities in training and professional practices of police women. The central question is how physical and lethal force produces contradictions between making progress careers and agreeing with expressions of femininity that inhibit, a priori, such skills. This paper is the result of an ethnographic fieldworkdisplayed over five years in different police Argentinian institutions.The fieldwork includes interviews and participant observation in training facilities and workplaces (police stations, patrols and special operations) of Argentina's Federal Police, Argentine National Gendarmerie, Buenos Aires Provincial Police and Argentine Naval Prefecture. Ethnographic descriptions discuss the idea of homogeneity of police culture and contribute to think about flexibility, permeability and diversity in the police profession. This article presents arguments and empirical data which lead to conceive police as a space of tensions regarding the conceptions of gender. On the one hand, police officers (males and females) reaffirm some hegemonic ideas of gender; on the other hand, in their speeches they break the traditional notion that femininity systematically implies weakness. In this sense, the display of physical force is incorporated by women in the course of their police careers and exercised in contexts of police actions, but reinterpreted when justifying their actions against judicial agents.